Rehabilitation after lumbar disc surgery - Oosterhuis, Teddy (Cochrane Database Syst Rev, 2014)
BACKGROUND: Several rehabilitation programmes are available for individuals after lumbar disc surgery. OBJECTIVES: To determine whether active rehabilitation after lumbar disc surgery is more effective than no treatment, and to describe which type of active rehabilitation is most effective. This is the second update of a Cochrane Review first published in 2002. First, we clustered treatments according to the start of treatment.  1. Active rehabilitation that starts immediately postsurgery.  2. Active rehabilitation that starts four to six weeks postsurgery.  3. Active rehabilitation that starts longer than 12 months postsurgery. For every cluster, the following comparisons were investigated.  A. Active rehabilitation versus no treatment, placebo or waiting list control.  B. Active rehabilitation versus other kinds of active rehabilitation.  C. Specific intervention in addition to active rehabilitation versus active rehabilitation alone. SEARCH METHODS: We searched CENTRAL (2013, Issue 4) and MEDLINE, EMBASE, CINAHL, PEDro and PsycINFO to May 2013. SELECTION CRITERIA: We included only randomised controlled trials (RCTs). DATA COLLECTION AND ANALYSIS: Pairs of review authors independently assessed studies for eligibility and risk of bias. Meta‐analyses were performed if studies were clinically homogeneous. The GRADE approach was used to determine the overall quality of evidence. MAIN RESULTS: In this update, we identified eight new studies, thereby including a total of 22 trials (2503 participants), 10 of which had a low risk of bias. Most rehabilitation programmes were assessed in only one study. Both men and women were included, and overall mean age was 41.4 years. All participants had received standard discectomy, microdiscectomy and in one study standard laminectomy and (micro)discectomy. Mean duration of the rehabilitation intervention was 12 weeks; eight studies assessed six to eight‐week exercise programmes, and eight studies assessed 12 to 13‐week exercise programmes. Programmes were provided in primary and secondary care facilities and were started immediately after surgery (n = 4) or four to six weeks (n = 16) or one year after surgery (n = 2). In general, the overall quality of the evidence is low to very low. Rehabilitation programmes that started immediately after surgery were not more effective than their control interventions, which included exercise. Low‐ to very low‐quality evidence suggests that there were no differences between specific rehabilitation programmes (multidisciplinary care, behavioural graded activity, strength and stretching) that started four to six weeks postsurgery and their comparators, which included some form of exercise. Low‐quality evidence shows that physiotherapy from four to six weeks postsurgery onward led to better function than no treatment or education only, and that multidisciplinary rehabilitation co‐ordinated by medical advisors led to faster return to work than usual care. Statistical pooling was performed only for three comparisons in which the rehabilitation programmes started four to six weeks postsurgery: exercise programmes versus no treatment, high‐ versus low‐intensity exercise programmes and supervised versus home exercise programmes. Very low‐quality evidence (five RCTs, N = 272) shows that exercises are more effective than no treatment for pain at short‐term follow‐up (standard mean difference (SMD) ‐0.90; 95% confidence interval (CI) ‐1.55 to ‐0.24), and low‐quality evidence (four RCTs, N = 252) suggests that exercises are more effective for functional status on short‐term follow‐up (SMD ‐0.67; 95% CI ‐1.22 to ‐0.12) and that no difference in functional status was noted on long‐term follow‐up (three RCTs, N = 226; SMD ‐0.22; 95% CI ‐0.49 to 0.04). None of these studies reported that exercise increased the reoperation rate. Very low‐quality evidence (two RCTs, N = 103) shows that high‐intensity exercise programmes are more effective than low‐intensity exercise programmes for pain in the short term (weighted mean difference (WMD) ‐10.67; 95% CI ‐17.04 to ‐4.30), and low‐quality evidence (two RCTs, N = 103) shows that they are more effective for functional status in the short term (SMD ‐0.77; 95% CI ‐1.17 to ‐0.36). Very low‐quality evidence (four RCTs, N = 154) suggests no significant differences between supervised and home exercise programmes for short‐term pain relief (SMD ‐0.76;  95% CI ‐2.04 to 0.53) or functional status (four RCTs, N = 154; SMD ‐0.36; 95% CI ‐0.88 to 0.15). AUTHORS' CONCLUSIONS: Considerable variation was noted in the content, duration and intensity of the rehabilitation programmes included in this review, and for none of them was high‐ or moderate‐quality evidence identified. Exercise programmes starting four to six weeks postsurgery seem to lead to a faster decrease in pain and disability than no treatment, with small to medium effect sizes, and high‐intensity exercise programmes seem to lead to a slightly faster decrease in pain and disability than is seen with low‐intensity programmes, but the overall quality of the evidence is only low to very low. No significant differences were noted between supervised and home exercise programmes for pain relief, disability or global perceived effect. None of the trials reported an increase in reoperation rate after first‐time lumbar surgery. High‐quality randomised controlled trials are strongly needed.